IMPLEMENTASI PENDELEGASIAN SEBAGIAN KEWENANGAN URUSAN PEMERINTAHAN KEPADA DINAS PENANAMAN MODAL DAN PELAYANAN TERPADU SATU PINTU KABUPATEN WONOGIRI - Joko Suranto, Adhityawahyu Wardana & (Master of Public Administration, Universitas Slamet Riyadi, 2018)
This Research aimed to analyze the implementation of to delegating part ofthe authirity of goverment affairs to Capital Investment and Integrated OneStop Service Office in Wonogiri Regency. This research was descriptiveresearch type. Capital Investment and Integrated One Stop Service Officein Wonogiri Regency Office (PMPTSP) was selected as the research site.Two kind of sampling techniques was implemented. First, purposivesampling technique was used to select the informants originating from theemployees of PMPTSP. Secondly, accidental sampling technique wasemployed to collect the data coming from the community opinions. In-depthinterview, direct observation, and documentation data collecting techniqueswere used. Interactive data analysis model as suggested by Miles andHubberman was employed in this research analysis. This interactiveanalysis model covers: data gathering, data reduction, data display, andconclusion drawing. Research results indicated that: 1. Relating to theaspect of communication, it was discovered that PMPTSP Office hasalready implemented to socialize its policies using some activities andemploying some existing information media and has already coordinatedwith the OPD Technique Unit. 2. Relating to the resources, research resultindicated that PMPTSP was lack of human resources, minimum budget,and deficiencies in the aspect structure and infrastructure for supportingservice. 3. In term of implementation aspect, it indicated that the apparatusof PMPTSP had clear commitment and responsibilities and supported thepolicy implementation. 4. Beureucratic and organizational structure did notsupported yet the implementation of the delegation part of governmentaffairs authority in field of service licenses and non-licenses. 5. Dealing witheconomic, social and political environtment, research result showed thatpeople in Wonogiri Regency supported the policy implementation, however,on the other hand, OPD less supported the implementation of to delegatingpart of the authirity of goverment affairs to Capital Investment andIntegrated One Stop Service Office in Wonogiri Regency.Key words: Communication; resource; delegation; authority; beureaucratic andorganizational structure; economic, social and political environtment.